Building the Universidad Nacional de Colombia Hospital: Reconciling social and academic aspects (2014)
In the process of building the National University Hospital, an analysis of the changing epidemiological profile of the population of Bogotá was undertaken, which examined the health care needs of the city, the academic needs of the university and institutional possibilities. It was made an analysis of the demographic and epidemiological profile of the population of Bogotá.It was concluded that there were factors associated with the epidemiological transition of aging, such as a low availability of health services for the elderly and diseases related to that care. Just as in the university, the hospital needs to develop all aspects of patient care to be able to adequately respond to the needs of this demographic from an interdisciplinary perspective, ensuring quality care based on the criteria of timeliness, accessibility, relevance, sufficiency, and continuity.A proposal is outlined concluding that the first phase of the portfolio of services that the University Hospital offers must be geared towards geriatric care and chronic illnesses, due to the aging of the general population as a result of a decline in fertility and mortality. This care would cater towards so-called permanent conditions that result in disability, or not easily reversible physiopathological conditions that require long-term care, as well as special training in secondary prevention and rehabilitation for the patient and the family.